Answer :

Let f(x) = x4 – 2x3 + 3x2 – ax + b

Now,

f(1) = 14 – 2(1)3 + 3(1)2 – a(1) + b

5 = 1 – 2 + 3 – a + b

3 = - a + b (i)

And,

f(-1) = (-1)4 – 2(-1)3 + 3(-1)2 – a(-1) + b

19 = 1 + 2 + 3 + a + b

13 = a + b (ii)

Now,

Adding (i) and (ii),

8 + 2b = 24

2b = 16

b = 8

Now,

Using the value of b in (i)

3 = - a + 8

a = 5

Hence,

a = 5 and b = 8

Hence,

f(x) = x4 – 2(x)3 + 3(x)2 – a(x) + b

= x4 – 2x3 + 3x2 – 5x + 8

f(2) = (2)4 – 2(2)3 + 3(2)2 – 5(2) + 8

= 16 – 16 + 12 – 10 + 8

= 20 – 10

= 10

Therefore, remainder is 10

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics